Chinese Special Needs Adoption, Demand, and the Global Politics of Disability - Erin Raffety (Disability Studies Quarterly, 2019)
This article explores three related phenomena: first, the abandonment and institutionalization of children with disabilities in China that increased disproportionately in the 2000s; second, the important relationships between such abandonments, culture, economics, and politics in contemporary China; and third, the relationship between such abandonments, the increasing rates at which Chinese orphans with disabilities are being adopted to Western countries through Inter-country Adoption (ICA), and the global politics of ICA and disability. Although the rise in the proportion of ICA from China of "children with special needs" is widely acknowledged, the reasons for the recent increase in abandonments of children with disabilities have been largely analyzed from the perspective of Chinese cultural views regarding disability (Holroyd 2003; Qian 2014), market economics (Wang 2016), the lack of Chinese government support for services for families (Shang 2008), as well as government coercion (Johnson 2016), thus, relatively divorced from the demand side of ICA. However, this article highlights the relationship between the disproportionate abandonment of children with disabilities in China and their increasing rate of ICA from China, arguing that discrimination toward persons with disabilities, or ableism, is not merely operative in abandonments of Chinese children with disabilities, but also embedded in the global politics of ICA.
Keywords: China; special needs; demand; child abandonment; inter-country adoption; ableism